SURVEY PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI DI SMA NEGERI 1 TAMAN - FERLINA TRI S (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Accounting learning process in SMA Negeri 1 Taman had been equipped with a LCD in each class, but the use of learning media of powerpoint was not maximied by teachers in presenting of accounting topic. This research aims to determine what was accounting learning media used by the teacher in class XI IPS SMA Negeri 1 Taman, to know what was the teacher reasons use that learning media, and to determine the feasibility of accounting learning media that used in class XI IPS SMA Negeri 1 Taman during learning process in the classroom. This research was a descriptive research. Data analysis techniques that used in this research were descriptive quantitative analysis techniques. The research results showed that learning media of powerpoint was feasible to use in accounting learning process at XI IPS in SMA Negeri 1 Taman with percentage of 72.05%. Keywords: learning media, accounting, SMA